Parasocial Interactions with Basketball Athletes of Color in Online Mediated Sports. Issue 2 (3rd April 2018) - Pan, Po-Lin; Zeng, Li
ABSTRACT: A two (Black athlete vs. Asian athlete) by two (Black viewer vs. Asian viewer) by two (male vs. female) mixed factorial experiment was designed to examine sports viewers' parasocial interaction (PSI) with basketball athletes of color. Results found that sports viewers were more likely to exhibit higher PSI when viewing athletes who belonged to their same racial group than viewing those from another racial group. Black viewers showed higher PSI with Black athlete than with Asian athlete. Correspondingly, Asian viewers reported higher PSI with Asian athlete than with Black athlete. Evidence for similarity identification suggested that the more similar media viewers were to media characters, the more likely media viewers were to develop affective bonds with media characters. In the context of online mediated sports, these affective bonds would direct sports viewers to desire greater similarity to athletes, activate them to take athletes' perspective, and eventually lead them to higher PSI with athletes in online mediated sports.